PENGARUH PEMBERIAN PUPUK ORGANIK CAIR ECENG GONDOK DAN LIMBAH KULIT PISANG TERHADAP PERTUMBUHAN DAN HASIL TANAMAN SELADA MERAH (Lactuca sativa var. Lollo rosa) PADA SISTEM HIDROPONIK NFT - Ahmad Shidiq; Yusnita Yusnita; Darwin H. Pangaribuan; R. A. Diana Widyastuti Widyastuti (Universitas Lampung, 2026)
Red lettuce can be planted hydroponically with the need of nutrient organic. This study aimed to examine the effect of substituting 25% of AB Mix nutrients with liquid organic fertilizer (LOF) made from water hyacinth or banana peels on the growth and yield of red lettuce cultivated using the NFT hydroponic system. The experiment was arranged in a Completely Randomized Design (CRD) with three treatments (100% AB Mix, 75% AB Mix + 25% water hyacinth LOF, and 75% AB Mix + 25% banana peels LOF) and six replications, each consisting of six plants. Growth parameters (plant height, number of leaves, leaf length, and leaf width) were observed weekly from 3 to 6 weeks after transplanting (WAT), while fresh and dry weights of shoots, leaves, and stems were measured at harvest (6 WAT). The obtained data were tested for homogeneity of variance using Bartlett's test, followed by analysis of variance and Least Significant Difference (LSD) test at 5% significance level when assumptions were fulfilled. The results showed that 75% AB Mix + 25% water hyacinth LOF were not significantly different from 100% AB Mix in terms of leaf number, stem fresh weight, as well as shoot, leaf, and stem dry weights, with shoot fresh weight reaching 92% and leaf fresh weight reaching 93% compared to 100% AB Mix. The treatment of 75% AB Mix + 25% banana peels LOF was able to match the growth and yield of the 100% AB Mix treatment.